(untitled) (Raparin Journal of Humanities (RJH), 2026)
This study presents a comparative analysis of Elif Shafak’s The Bastard of Istanbul (2006) and Gharbi M. Mustafa’s What Comes with the Dust (2016) to explore how these texts – written by two authors from different genders and ethnic backgrounds – depict displacement as a paradoxical tool for female liberation, giving voices to their ongoing struggles. The research examines that women in these two literary works suffer the pain of unbelonging due to dominant exclusionary discourses and that they seek settlement through self-displacement. By means of a critical framework informed by Third Wave Feminism and the postcolonial discussions, this paper examines womanhood in Turkish, Kurdish, and Armenian patriarchal communities in the texts under analysis. Furthermore, the study establishes historical linkages between female experiences – Armanoush and Nazo – being exposed to atrocities during the Armenian Genocide in 1915 and ISIS attacks on Yezidis in 2014. By means of applying comparative tools of analysis, the study investigates how social and historical legacies shape the representation(s) of women, focusing on their shared experiences of rape, slavery, and abuse across different geographical and cultural landscapes. This research argues that these authors utilize the traumatic experience of displacement not only to expose gendered violence but also to chart a path toward reconstructed identity and hard-won autonomy for their female characters.